A Lactate Fermentation Mutant of Toxoplasma Stimulates Protective Immunity Against Acute and Chronic Toxoplasmosis - Xia, Ningbo; Zhou, Taifang; Liang, Xiaohan; Ye, Shu; Zhao, Pengfei; Yang, Jichao; Zhou, Yanqin; Zhao, Junlong; Shen, Bang (Frontiers in Immunology, 2018)
Toxoplasma gondii is an important zoonotic pathogen infecting one-third of the world’s population and numerous animals, causing significant healthcare burden and socioeconomic problems. Vaccination is an efficient way to reduce global sero-prevalence, however ideal vaccines are not yet available. We recently discovered that the Toxoplasma mutant lacking both lactate dehydrogenases LDH1 and LDH2 (Δldh) grew well in vitro but was unable to propagate in mice, making it a good live vaccine candidate. Here we tested the protection efficacy of ME49 Δldh using a mouse model. Vaccinated mice were efficiently protected from the lethal challenge of a variety of wild type strains, including type 1 strain RH, type 2 strain ME49, type 3 strain VEG, and a field isolate of Chinese 1. The protection efficacies of a single vaccination were nearly 100% for most cases and it worked well against the challenges of both tachyzoites and tissue cysts. Re-challenging parasites were unable to propagate in vaccinated mice, nor did they make tissue cysts. High levels of Toxoplasma specific IgG were produced 30 days after immunization and stayed high during the whole tests (at least 125 days). However passive immunization of naïve mice with sera from vaccinated mice did reduce parasite propagation, but the overall protection against parasite infections was rather limited. On the other hand, Δldh immunization evoked elevated levels of Th1 cytokines like INF-γ and IL-12, at early time points. In addition, splenocytes extracted from immunized mice were able to induce quick and robust INF-γ and other pro-inflammatory cytokine production upon T. gondii antigen stimulation. Together these results suggest that cellular immune responses are the main contributors to the protective immunity elicited by Δldh vaccination, and humoral immunity also contributes partially. We also generated uracil auxotrophic mutants in ME49 and compared their immune protection efficiencies to the Δldh mutants. The results showed that these two types of mutants have similar properties as live vaccine candidates. Taken together, these results suggest that mutants lacking LDH were severely attenuated in virulence but were able to induce strong anti-toxoplasma immune responses, therefore are good candidates for live vaccines.